HUBUNGAN SIKAP DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATEMATIKA KELAS IV A - Ela Riska Aulia; Suparjan Suparjan; Rio Pranata (Universitas Tanjungpura, 2021)
AbstractRelationship learning attitudes and learning motivation with mathematics learning outcomes in grade IV A. The research method used is descriptive method of preliminary study research. The population in this study amounted to 24 students and the sample used was class IV A totaling 24 students. Data collection techniques study are indirect communication techniques and documentary study techniques. The instrument of this study was in the form of a questionnaire and a mid-semester math test score document. The results showed that student learning attitudes at amounted to 72.55% in the